2013
DOI: 10.1001/jamaophthalmol.2013.202
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcomes and Cost Basis for Resident-Performed Cataract Surgery in an Uninsured Patient Population

Abstract: IMPORTANCEIn the past, resident physicians have provided care to indigent patients under the supervision of experienced physicians. General consensus exists regarding higher surgical costs of patient care at teaching hospitals. No study has examined the outcomes or the cost basis for resident physicians providing health care to an underserved population.OBJECTIVES To evaluate the visual results in uninsured patients undergoing cataract surgery performed by resident surgeons at a single institution and to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 53 publications
0
3
0
1
Order By: Relevance
“…[18][19][20][21] So, for the betterment of surgical outcomes, audit and re audit should be conducted. [22][23][24][25] Postoperative VA was recorded for 982 (100%) eyes. After cataract surgery, 966 (98.4%) eyes had good VA compared with pre-operative measurements.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21] So, for the betterment of surgical outcomes, audit and re audit should be conducted. [22][23][24][25] Postoperative VA was recorded for 982 (100%) eyes. After cataract surgery, 966 (98.4%) eyes had good VA compared with pre-operative measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Smith et al Studies have demonstrated that resident involvement can improve cost-effective medical care without changing patient care outcomes. 12 Similarly, positive resident-nurse interactions can improve patient safety, quality of care, provider and nurse satisfaction and healthcare costs, which can be facilitated by increased availability and receptiveness to communication. 13,1 The resident-nurse relationship is impacted uniquely in different specialties.…”
Section: Introductionmentioning
confidence: 99%
“…3 Several published studies report on the rates of intraoperative and postoperative complications in resident-performed surgeries, however few report on visual and especially anatomic outcomes. [3][4][5] Making use of department-maintained morbidity and mortality records as well as visual acuity and OCT data, the purpose of the current study is to assess the visual and anatomic outcomes of resident-performed cataract extractions in cases with intraoperative or major postoperative complications.…”
Section: Introductionmentioning
confidence: 99%